2013
DOI: 10.1016/j.neuroimage.2013.02.073
|View full text |Cite
|
Sign up to set email alerts
|

Differential connectivity within the Parahippocampal Place Area

Abstract: The Parahippocampal Place Area (PPA) has traditionally been considered a homogeneous region of interest, but recent evidence from both human studies and animal models has suggested that PPA may be composed of functionally distinct subunits. To investigate this hypothesis, we utilize a functional connectivity measure for fMRI that can estimate connectivity differences at the voxel level. Applying this method to whole-brain data from two experiments, we provide the first direct evidence that anterior and posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
117
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(149 citation statements)
references
References 58 publications
30
117
2
Order By: Relevance
“…Note that our hypothesis of two distinct systems for human scene processing – a categorization system including PPA, and a navigation system including RSC and OPA – does not mean that the two systems cannot and do not interact. Indeed, two recent studies found functional correlations between the RSC and anterior portions of the PPA, and between the OPA and posterior PPA (Baldassano et al 2013; Nasr et al 2013), suggesting these two regions are functionally (and most likely anatomically) connected, thereby facilitating crosstalk between the two systems.…”
Section: Discussionmentioning
confidence: 99%
“…Note that our hypothesis of two distinct systems for human scene processing – a categorization system including PPA, and a navigation system including RSC and OPA – does not mean that the two systems cannot and do not interact. Indeed, two recent studies found functional correlations between the RSC and anterior portions of the PPA, and between the OPA and posterior PPA (Baldassano et al 2013; Nasr et al 2013), suggesting these two regions are functionally (and most likely anatomically) connected, thereby facilitating crosstalk between the two systems.…”
Section: Discussionmentioning
confidence: 99%
“…It seems reasonable that an additional representation in ventral pathway might serve to bring scene information into close interaction with object information, to enhance understanding of objects in environmental contexts. There is human fMRI evidence that scene and object information are brought together in the lateral occipital complex [22], a likely homologue for macaque higher-level ventral pathway, as well as in PPA and RS [2327]. …”
Section: Discussionmentioning
confidence: 99%
“…For instance, both task-based (Pessoa et al 2006; Almeida et al 2013; Mahon et al 2013; Garcea & Mahon 2014) and resting functional connectivity (Zhang et al, 2009; Turk-Browne et al, 2010; Zhu et al, 2011; Simmons & Martin, 2012; Baldassano et al, 2013; He et al, 2013; Hutchison et al, 2014; O’Neil et al, 2014; Stevens, et al, 2015; Wang et al, 2015), as well as structural connectivity (Saygin et al, 2011; 2016; Mars et al, 2012; Bouhali et al, 2014; Osher et al, 2015), suggest alignment between stimulus preferences and connectivity to regions outside the ventral stream (for discussion of a connectivity-constrained account of category specificity, see Riesenhuber 2007; Martin, 2006; 2009; Mahon & Caramazza 2011; Chen & Rogers 2014; Behrmann & Plaut 2013; Mahon et al, 2007; 2009; Mahon, 2015). …”
Section: Introductionmentioning
confidence: 99%